GABAergic modulation of secondary hyperalgesia: A randomized controlled 4‐way crossover trial with the α2‐subunit preferring GABA positive allosteric modulator, N‐desmethyl‐clobazam in healthy volunteers. (1st April 2020) - Matthey, Alain; Daali, Youssef; Curtin, François; Poncet, Antoine; Desmeules, Jules; Besson, Marie
Abstract: The antihyperalgesic and sedative effects of the α2‐subunit preferring GABAA positive allosteric modulator (GAM), N ‐desmethyl‐clobazam (NDMC), 20 and 60 mg, were assessed in a randomized, placebo and active‐controlled (clonazepam 1, 5 mg), 4‐way crossover study, in healthy volunteers, using the ultraviolet B‐induced experimental pain model. Single (20, 40, 60 mg) and repeated doses (20 mg over 15 days) of NDMC pharmacokinetics were evaluated. Thirty‐two subjects participated in the study. Primary outcome parameter was maximal change in the area of cutaneous UVB irradiation‐induced secondary hyperalgesia (ASH). ASH decreased under all treatments. Mean ( SD ) relative change was 79 (22)%, 83 (24)%, 77 (30)% and 92 (16)% for placebo, NDMC20, NDMC60 and clonazepam, respectively. Neither absolute change nor relative change in ASH was significantly different between NDMC60 and placebo (mean difference = 2.3 cm 2 [95% CI 4.0–8.5], p  = .462 and 0.4% [−11.9 to 12.6], p  = .952, respectively). An overall treatment effect was found on level of sedation. Compared to placebo, sedation was higher under clonazepam (mean difference = 39 mm [30–49] on a visual analogue scale, p  < .001) while NDMC was free of sedative effect. NDMC pharmacokinetics after single doses showed poor absorption, but was linear. Steady‐state plasma concentrations of NDMC20 were attained within 14 days, with low between‐subjects variability. Mean steady‐state concentration ( C S‐S, SD ) reached 209 (22) ng/ml. NDMC absence of sedative effect and its overall well‐characterized safety coming from years of utilization as a metabolite from clobazam, raise the prospect of dose escalating trials in patients to quantify its clinical utility. Significance: This article, presenting the Phase I data of the new antihyperalgesic compound, α2‐subunit GABAA positive allosteric modulator, N ‐desmethyl‐clobazam (NDMC) is exploring the modulation of a new target in the treatment of neuropathic pain. Based on these results and on its preclinical properties NDMC would qualify as a good tool compound to seek confirmation of the clinical utility of selective GABA allosteric modulators in neuropathic pain patients.